Lethal persistent pulmonary hypertension of the newborn in Bohring–Opitz syndrome. Issue 5 (21st April 2018) - Kibe, Masaya; Ibara, Satoshi; Inagaki, Hidehito; Kato, Takema; Kurahashi, Hiroki; Ikeda, Toshiro
Abstract : Bohring–Opitz syndrome (BOS) is a rare disease with a number of characteristic features, including hypertelorism, prominent metopic suture, exophthalmos, cleft palate, abnormal posture, and developmental retardation. Here, we report a BOS patient presenting with lethal persistent pulmonary hypertension of the newborn (PPHN) and inspiratory respiratory failure. The female infant was treated with nitric oxide and vasodilator, which did not improve her condition. The inspiratory respiratory failure required management with deep sedation. She died on postnatal day 60 due to progressed heart failure. Whole exome sequencing revealed de novo mutation in the ASXL1 gene, c.1934dupG, p.Gly646TrpfsTer12.